Estudo reprodutivo de filostomídeos em fragmentos de mata atlântica no estado do Paraná, sul do Brasil - Jorge, Thaiz Martinez Rodrigues (2016)
Bats have different strategies from other similarly sized animals, presenting longstanding life with multiple reproduction events, small number of offsprings per pregnancy and late sexual maturity, and their reproductive patterns related to endogenous and exogenous factors. For these animals, energy costs are high during reproduction, and even more, during lactation, which seems that this one, the most expensive part energy coincides with the availability of resources and the period of higher rainfall. Understanding the factors that contribute to the growth of bat populations can be an important tool for the development of appropriate conservation strategies, as anthropic activities may directly affect the existence of these bats. This study aimed to analyze the reproductive aspects of bats of species Artibeus lituratus, Carollia perspicillata and Sturnira lilium in Atlantic forest fragments (Parque Estadual Vila Rica do Espírito Santo, Fênix- Fênix, Porto Rico - PR and Parque Cinturão Verde de Cianorte - PCV) in the state of Paraná, southern Brazil, , and relate them to dry and rainy seasons. Thus, the following hypotheses are: 1) In the rainy season, due to its greater availability of food resources, there will be higher catch values of reproductive females; 2) Artibeus lituratus, for being endowed with great adaptive capacity and feeding plasticity presents vaster reproductive period with female reproductive in most of the sampling period. Data on sex, reproductive stage and months in which occurred the samples were obtained from previous studies that occurred from July 2002 to June 2003 (PEVR), from January to December 2006 (MPR) and from April 2009 to March 2010 (PCV) and temperature and rainfall granted by the Technological Institute SIMEPAR. It was observed that the rainy season had the highest temperatures and rainfall amounts, and has been marked by the highest number of total catch of phyllostomide, especially pregnant and lactating females, which indicates a reproductive trend of the species under study, for this season. It was also observed that A. lituratus for adapting well to anthropogenic changes, introduced reproductive females in all sampled months. In conclusion, the species of bats studied are influenced by abiotic factors in relation to its reproduction, preferring thus holding it in periods of higher rainfall and temperature during the rainy season, as this has the best conditions for the development of the pups.